The Impact of Customer Loyalty Programme on Apparel Retail in India - Kulkarni, Pranav (Global journal of Business and Integral Security, 2025)
This study explores the impact of customer loyalty programmes (CLPs) on customer retention and sales performance within the apparel retail industry in India. The study aims to understand the role of loyalty programme benefits, customer satisfaction, engagement, trust, and emotional connection in influencing consumer behaviour. Employing a mixed-methods approach, quantitative data was gathered from 201 customers through structured surveys, while qualitative insights were obtained from in-depth interviews with three loyalty programme managers representing prominent apparel brands. Quantitative analysis revealed a significant relationship between loyalty programme factors and customer retention. Regression results showed that loyalty programme benefits and customer satisfaction were the most critical predictors, while engagement, trust, and emotional connection played less substantial roles. The model demonstrated strong explanatory power, with an R² value of 79.3%, indicating that loyalty programme factors accounted for a substantial variance in customer retention and sales. Qualitative findings from interviews highlighted industry trends such as a growing emphasis on experiential loyalty offers, the importance of data analytics for personalization, and innovative strategies for engaging lapsed customers. Managers emphasized the need for flexible reward structures and trust-building practices to foster long-term relationships. The study concludes that loyalty programmes significantly impact customer retention and sales when designed to meet consumer needs through personalized incentives, consistent engagement, and transparent policies. However, gaps in engagement and emotional connection suggest opportunities for improvement. This research contributes to academic discourse by integrating quantitative and qualitative insights to offer a comprehensive understanding of loyalty programme dynamics in the Indian apparel sector. Practical recommendations include refining reward structures, enhancing personalization through advanced analytics, and leveraging experiential incentives to strengthen customer-brand relationships. By addressing these aspects, the study provides actionable insights for apparel retailers aiming to maximize the effectiveness of their loyalty programmes and sustain competitive advantages in a dynamic market.